Antineoplasic and immunological potential of the african milker (Synadenyum grantii hook) in patients with risk factors for Covid-19 - Roque Rodríguez, Francisco Javier (2020)
New and little known plant species with desirable functional properties have been reported in the literature in recent years due to a growing interest in obtaining and applying bioactive compounds and metabolites derived from their cellular structures within the context of natural and ecological medicine. Synadenyum grantii Hook, commonly known as African milker, has been used for the treatment of common and degenerative diseases in human metabolism through the extraction of its latex that has been studied for its bioactive components where the phorbol is the one that presents restorative activity and cell regenerator. In this main aspect, the latex of the African milker has shown an antineoplastic potential increase and strengthens the immune system in humans with risk factors such as cancer and / or immunosuppressive patients, for which it has received the nickname of 'plant of life' as an indicator of its beneficial effects in the treatment of these diseases. In the literature review carried out, numerous publications have been found that report success in its application in a natural way and as an active principle in patients with malignant tumors and in the antiproliferative response of cancer cells, avoiding final stages of metastasis;but, in the current conjuncture of the SARS-CoV-2 coronavirus pandemic, the African milker through its latex has found applications recently described as an enhancer of the immune system of this interest group with a risk factor for the disease of COVID- 19 that would have a positive impact on the fight against the effects of this virus in our country and throughout the world.